Analisis Pengaruh Rasio Likuiditas, Rasio Profitabilitas, Rasio Solvabilitas Dan Rasio Pasar Terhadap Return Saham: (Studi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2011 - 2013 - Jaunanda, Meliana; Fransesca, Baby Amelia (Universitas Multimedia Nusantara, 2015)
The objective of this research is to examine the effect of liquidity ratio, profitability ratio, solvabilitas ratio and market ratio both partially and simultaneously towards stock return. The liquidity ratio is proxied by Current Ratio; the profitability ratio is proxied by Return On Assets; the solvabilitas ratio is proxied by Debt to Equity Ratio and the market ratio is proxied by Price to Book Value. The testing method used in this research is linear regression.The objects of this study are manufacturing companies sub sector chemical which were listed in Bursa Efek Indonesia in the period 2011-2013. The samples are 20 companies determined based on purposive sampling. The data used in this study are secondary data such as financial statements and stock prices.The results of this study are (1) profitability ratio is proxied by Return On Assets partially have a significant effect towards stock return. (2) liquidity ratio proxied by Current Ratio partially, profitability ratio is proxied by Return On Assets; solvabilitas ratio is proxied by Debt to Equity Ratio and market ratio is proxied by Price to Book Value simultaneously have a significant effect towards stock return. Profitability ratio is proxied by Return On Assets partially have a significant effect towards stock return. Keywords: Current Ratio (CR), Debt to Equity Ratio (DER), liquidity ratio, market ratio, Price to Book Value (PBV), profitability ratio, Return On Assets (ROA), solvabilitas ratio, stock return.